Tracing the origin of olive ridley turtles entangled in ghost nets in the Maldives: A phylogeographic assessment of populations at risk. (May 2020) - Stelfox, Martin; Burian, Alfred; Shanker, Kartik; Rees, Alan F.; Jean, Claire; Willson, Maïa S.; Manik, Nashwa Ahmed; Sweet, Michael
Abstract: Abandoned, lost or discarded fishing gear, (ghost nets) represent a major threat to marine vertebrates. However, thorough assessments of their impact on threatened species are largely missing. In the Maldives, olive ridley sea turtles ( Lepidochelys olivacea ) are frequently caught in ghost nets however the archipelago does not support a significant nesting population. Our aim in this study was to determine the origin of olive ridleys entangled in ghost nets found in the Maldives and evaluate potential impacts on respective source populations. Based on a citizen science and conservation program, we recorded 132 olive ridley turtles entangled in ghost nets in just one year. Genetic analyses (mtDNA) of entangled individuals and of potential source populations revealed that most captured olive ridleys originated from Sri Lanka and eastern India. Oman could be excluded as a source population, even during the prevalence of the south west monsoon. Based on our results and already available published literature, we were able to estimate that the recorded ghost net entanglements accounted for a relatively small amount (0.48%) of the eastern Indian population. However, the entangled turtles accounted for a much larger percentage (41%) of the Sri Lankan populations. However, it should be noted that our estimates of population-level mortality are linked to substantial uncertainty due to the lack of reliable information on population dynamics. Consequently, any precautionary protection measures applied should be complemented with improved quantification of turtle recruitment and life-stage specific mortalities.